O discurso educacional do Maranhão na Primeira República: uma análise de conteúdo - Andrade, Beatriz Martins de (1982)
Departing from the viewpoint that the Maranhense society of the First Republic knew a well – defined social division of work in which the dominant classes deliberately detained knowledge in the sphere of power, this paper undertakes a study of the historical reconstitution of society of the times as well as its educational system in an attempt to contextualize the analysis of discourse of several Maranhenses intellectuals, clarifying their eminently conservative character and pointing out their compromise with the structures of power of the State in their attempt to transmit the official ideology; and in so doing provoke the alienation of the masses. With the advent of the Republic, education became increasingly important in its role as reproductor of the structures of power, as inculcator of the ideology of the dominant classes and as breeder of social differences between individuals. These concepts are discussed and analyzed in the following thesis.